2014
DOI: 10.1377/hlthaff.2014.1021
|View full text |Cite
|
Sign up to set email alerts
|

San Francisco Children Living In Redeveloped Public Housing Used Acute Services Less Than Children In Older Public Housing

Abstract: Understanding the links between housing and health is increasingly important. Poor housing quality is a predictor of poor health and developmental problems in low-income children. We examined associations between public housing type and recurrent pediatric emergency and urgent care hospital visits. Children ages 0-18 with public insurance who sought emergency care from any of three large medical systems in San Francisco were categorized by whether they lived in public housing redeveloped through the federal HO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Some studies attempted to use validated questionnaires for material needs. Most studies were cross‐sectional surveys, five were retrospective cohort studies, and three used prospective cohorts . Several studies described their methods as “case‐control” or “prospective” but were in fact cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Some studies attempted to use validated questionnaires for material needs. Most studies were cross‐sectional surveys, five were retrospective cohort studies, and three used prospective cohorts . Several studies described their methods as “case‐control” or “prospective” but were in fact cross‐sectional.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported a range of 18.1% to 43.8% of patients residing in variably defined unstable housing situations . A few studies included living in public or subsidized housing as housing‐related variables …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…18 For instance, poor housing is linked to health status. 19,20,21 A child with asthma living in housing with cockroach infestation or mold will require assistance from social workers, legal advocates and housing organizations to reduce allergen exposure and improve health. Addressing these new vital signs will require research on effective screeners and interventions, partnerships with community organizations and appropriate payment for screening and management.…”
Section: “Diagnose Disparities” In Clinical Encounters and Innovate Nmentioning
confidence: 99%